Identification of 'Candidatus phytoplasma ziziphi' associated with persimmon (Diospyros kaki Thunb.) fasciation in China. Issue 4 (13th May 2015) - Wang, J.; Gao, R.; Yu, X. M.; An, M.; Qin, Z. H.; Liu, J.; Ai, C. X.; Woodward, S.
Summary Persimmon (Diospyros kaki Thunb.) trees, with fasciation symptoms (PF), were observed in an orchard located in suburban Tai'an, Shandong Province, China. A specific fragment of the phytoplasma 16S rRNA gene, approximately 1.2 kb in length, was amplified from two symptomatic plants via nested polymerase chain reaction, while no fragment was obtained from healthy controls. The two samples (PF1 and PF2) resulted with 99.5% nucleotide sequence identity. Phylogenetic and restriction fragment length polymorphism (RFLP) analysis of 16S rRNA gene sequences revealed that PF1 was a member of ribosomal subgroup B of the elm yellows group (16SrV), and PF2 may represent a novel subgroup within the 16SrV group, designed as 16SrV‐I. This is the first report of phytoplasmas of the 16SrV group associated with persimmon fasciation disease.